2014
DOI: 10.1002/anie.201311291
|View full text |Cite
|
Sign up to set email alerts
|

Confining Phosphanes Derived from Cyclodextrins for Efficient Regio‐ and Enantioselective Hydroformylation

Abstract: Two confining phosphane ligands derived from either α- or β-cyclodextrin produce singly P(III) -ligated metal complexes with unusual coordination spheres. High-pressure NMR studies have revealed that rhodium hydride complexes of the same type are also formed under hydroformylation conditions. This unique feature strongly favors the formation of the branched aldehyde at the expense of the linear one with high enantioselectivity in the rhodium-catalyzed hydroformylation of styrene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(44 citation statements)
references
References 70 publications
1
42
1
Order By: Relevance
“…The encapsulated Rh-α⊂4·(BArF) 8 catalyst exhibits among the highest selectivities in the asymmetric hydroformylation of styrenes for monoligated rhodium catalysts. 6 Most significantly, stereoselectivity observed in the hydroformylation of styrenes upon encapsulation of the catalyst are substantially improved with regard to analogous reactions performed with the catalyst operating in bulk solution. Therefore, the cage can be considered as a second coordination sphere of the catalyst, and its role may be understood as reminiscent of enzymatic active sites.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The encapsulated Rh-α⊂4·(BArF) 8 catalyst exhibits among the highest selectivities in the asymmetric hydroformylation of styrenes for monoligated rhodium catalysts. 6 Most significantly, stereoselectivity observed in the hydroformylation of styrenes upon encapsulation of the catalyst are substantially improved with regard to analogous reactions performed with the catalyst operating in bulk solution. Therefore, the cage can be considered as a second coordination sphere of the catalyst, and its role may be understood as reminiscent of enzymatic active sites.…”
Section: Resultsmentioning
confidence: 99%
“…The encapsulated catalyst gives among the highest chemo and stereoselectivities for a monoligated rhodium complex reported so far. 6 Using an incubation period at 40 ºC before initiating the reaction resulted in a higher TON, at the expense of the selectivity (TON from 797 to 1600, ee from 74 to 65%; see entries 1 and 6).…”
Section: α⊂4·(barf)mentioning
confidence: 99%
See 1 more Smart Citation
“…Jouffroy et al [20,21] have reported obtaining cyclodextrin-based cavity-shaped ligands to generate exclusively singly-phosphorus-ligated complexes. Such complexes with rhodium when being used to catalyze the hydroformylation of styrene led to high iso-regioselectivity and stereoselectivity (Scheme 6).…”
Section: Methodsmentioning
confidence: 99%
“…[2][3][4][5][6][7] Alterations in regioselectivity were observed with encapsulated metal catalysts in hydratation or hydroformylation reactions. [8][9][10][11] An unusual coordination mode of the complex imposed by the confinement, or a controlled approach of the substrate imposed by sterics have been raised to explain the changes. Hence, regioselectivity is influenced by confinement of the reactive center but the reaction mechanism itself was not invoked.…”
mentioning
confidence: 99%